Data inventory of students' research skills to support SDGs at junior high school - Haqiqi, Baharudin Yusuf; Kusnadi, Kusnadi; Kusumastuti, Mimin Nujhani (Assimilation: Indonesian Journal of Biology Education, 2025)
This research is aimed at gathering data on students' research skills in supporting the SDGs (Sustainable Development Goals) at the secondary school level. This study is a quantitative descriptive research using a survey method to map students' research skills in one of the schools in Bandung city. The population of this research consists of 7th-grade students who have studied the subject of Hakikat Sains dan Metode Ilmiah (n=52). The results of this study describe students' knowledge of SDGs and their research skills related to SDG-oriented issues. The data found indicate that while many students have heard of SDGs, there is still a need for improvement. Furthermore, the results regarding research skills show that many students understand how to conduct research. However, for each indicator, there is still a data spread or unequal distribution of scores between high and low groups in research skills. Therefore, efforts are still needed to improve students' research skills so they can actively contribute to solving problems